2004
DOI: 10.1159/000077912
|View full text |Cite
|
Sign up to set email alerts
|

Right Precordial and Posterior Electrocardiographic Leads Do Not Increase Detection of Ischemia in Low-Risk Patients Presenting with Chest Pain

Abstract: Background: A number of innovative approaches have been investigated for their value in the early detection of acute ischemia or infarction in patients presenting to the emergency department (ED) with chest pain suggestive of a cardiac origin. Prior investigations have demonstrated the utility of adding right precordial and posterior chest leads to the standard 12-lead electrocardiogram (ECG) for identifying right ventricular and posterior wall infarctions in the ED. Hypothesis: To assess the utility of additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Zalenski et al (1993) found that the addition of leads V4R, V8, and V9 in patients with a provisional diagnosis of MI or unstable angina increased the sensitivity of ST-segment elevation detection from 47.1% to 58.8%, with no loss of specificity. In a study of low-risk patients with chest pain suggestive of acute coronary syndromes, however, posterior leads were not found to increase the detection rate of ischemia (Ganim et al, 2004).…”
Section: Introductionmentioning
confidence: 85%
“…Zalenski et al (1993) found that the addition of leads V4R, V8, and V9 in patients with a provisional diagnosis of MI or unstable angina increased the sensitivity of ST-segment elevation detection from 47.1% to 58.8%, with no loss of specificity. In a study of low-risk patients with chest pain suggestive of acute coronary syndromes, however, posterior leads were not found to increase the detection rate of ischemia (Ganim et al, 2004).…”
Section: Introductionmentioning
confidence: 85%
“…In a study of low-risk patients presenting with chest pain suggestive of acute coronary syndromes, posterior leads were not found to increase the detection rate of ischemia [28]. Low-risk patients were identified by a normal 12-lead ECG, absence of arrhythmias or hemodynamic instability, and one negative serum cardiac troponin I assay.…”
Section: Posterior Leadsmentioning
confidence: 94%
“…These additional leads were not useful in detecting ischemia or injury in the resting ECG in patients admitted to our CPEU. 38 A notable aspect of our CPEU experience has been the high recidivism rate of patients discharged from our unit with a negative evaluation. During a 7.5-year period, 13% of 1960 patients had Ն2 or more negative immediate exercise tests and accounted for 26% of the CPEU visits.…”
Section: Immediate Exercise Testing In Subpopulationsmentioning
confidence: 98%